Optimization and regulation of pavement concrete properties in plateau environment with large daily temperature difference: From mixture design to field application. (16th May 2023) - Cui, Tong; Zhang, Tongsheng; Wang, Jinnan; Chen, Jie; Wang, Wei; Wang, Hongtai; Wang, Huibin; Yang, Donglai
Highlights: Mixture proportion of pavement concrete was optimized to improve cracking resistance. Surplus mortar coefficient should be controlled in 1.48–1.75. On-site paving of concrete was carried out in a large temperature variation and high-speed wind environment. The temperature difference and internal strain of pavement with thickness of 30 cm were controlled within 4.0 °C and 57 ε. No visible crack was observed for pavement with area of 400 m 2 . Abstract: Cement concrete pavement has been widely utilized in road engineering in western China due to its low cost, easy maintenance, and long service life. However, the properties of pavement concrete were very sensitive to the local environment, particularly for high-speed wind and large daily temperature difference. This study aims to regulate the workability and mechanical properties of pavement concrete from mixture proportion design, then on-site paving was carried out to validate the feasibility of field application. Although the cement paste volume ratio decreased from 25.4% to 21.3%, target compressive strength (40 MPa) of pavement concrete was achieved by optimizing the gradation of fine and coarse aggregates. And the volume stability of pavement concrete was improved after replacing 8% of Portland cement by limestone powder. For field application in a plateau environment with daily temperature difference around 20 °C and wind-speed of 5.5–7.0 m/s, the temperature difference and internal strain of concrete pavement with thickness of 30 cm were controlled within 4.0 °C and 57 ε, respectively. More importantly, no visible cracks were observed for concrete pavement with surface area of 400 m 2 . The results provided a feasible approach to design and regulate the mixture of pavement concrete with superior cracking resistance, and then promoted the application of concrete pavement in high expressway engineering in severe environment.